POTENSI TEMPE (RHYZOPUS.SP) SEBAGAI SUMBER PHYTOESTROGENS UNTUK MENGAKTIFKAN DAN MENCAPAI SEL STEM DALAM PERBAIKAN LENSA KATARAK DAN PERBAIKAN METANOLIK DARI EKSTRAK GARLIC (ALLIUM SATIVUM) SEBAGAI TERAPI TERAPI DALAM KATAK DIABETIK - Ihsan Otriami; Devin Mahendika; Dio Jainata (Journal Medical Universitas muhammadiyah Makassar, 2019)
Cataracts are turbidity lenses that are normally transparent and light is passed through to the retina, which is caused by various things resulting in impaired vision. One of the causes of cataract is diabetes mellitus which manifests clinically as hyperglycemia. Various therapies have been developed to deal with cataracts. However, the therapy is a definitive form of surgery which causes long-term complications in the form of blindness. One of the therapeutic modalities developed today is stem cell therapy. Stem cells are undifferentiated cells and have high potential to become other cells. Stem cells can differentiate to repair damaged lentic capsules and the formation of subepithelial lamellar fibers. Stem cells proliferate and migrate will be assisted by estrogen. However, the use of estrogen often causes bad side effects for the body. So, estrogen replacement is needed which has the same effect but does not produce side effects.Tempe is a typical Indonesian food that has isoflavonoid content. Isoflavonoids are able to function as phytoestrogens in the human body and have the same function as 17β-estradiol. In stem cells, phytoestrogens will play a role in activating paracrine actin (Akt) and stromal cell derived-1 (SDF-1) signals. Phytoestrogens will accelerate the rate of mesenchymal stem cell (MSC) / induced pluripotential stem cell (iPSC) and bind to the right receptors, so as to increase the work effectiveness of stem cells. Meanwhile, in diabetic cataract conditions the potential for garlic methanolic has recently been developed in relation to antioxidant effects, effective hypoglycemic and scavenging oxidative stress factors such as H2O2 and decreasing protein fraction in the lens due to protein insolubility. Keywords : Tempe, Stem Cell, Phytoestrogens, Garlic, and Metanolic.